Edge shape effect on switching behavior in a small ferromagnetic pattern - Kwon, Jae Hyun; Koo, Hyun Cheol; Yi, Hyunjung; Han, Suk-Hee (ADVANCES IN NANOMATERIALS AND PROCESSING, PTS 1 AND 2, 2007)
Switching behavior and domain structure greatly depends on the edge shape of mesoscopic patterns. In our simulation, permalloy patterns with elliptical and tapered edge need 80% and 50% more switching field, respectively, than a rectangle for the same overall aspect ratio of four. In the switching dynamics, vortex nucleation and its initial location play a great role in deciding switching field. Elliptical and tapered patterns show high magnetic remanence, which is advantageous for non-volatile device application. It is also demonstrated that small control of tapered edge makes it possible to change the switching behavior without the variation of overall aspect ratio.